OPTIMASI PENGAWASAN OLEH OTORITAS JASA KEUANGAN DI BIDANG PASAR MODAL MENURUT HUKUM POSITIF DI INDONESIA - WISUDAWAN, I GUSTI AGUNG; SUTRISNO, BUDI; MULADA, DIMAN ADE (GANEC SWARA, 2021)
The development of the capital market in Indonesia has increased from time to time but this development is not without obstacles. The obstacle that often arises is the occurrence of fraudulent practices in the capital market involving legal subjects in the capital market itself. Therefore, it is necessary to optimize supervision by the OJK in the Capital Market sector to minimize this fraudulent practice. The type of research used in this research is Normative Research with a statutory approach (Statute Approach), Conceptual Approach (Conceptual Approach), Case Approach (Case Approach), and Analysis Approach (Analytical Approach). This study also uses legal materials which consist of primary legal materials, namely legal materials in the form of Law No. 8 of 1995 concerning the Capital Market and OJK laws and regulations, secondary legal materials, namely literature related to the issues raised in this study and materials. Tertiary Law consists of a legal dictionary and encyclopedia. Legal material collection techniques used in this research is a Documentation Study with Legal Material Analysis, namely Qualitative Descriptive Analysis.       The results of this study are Optimization of Supervision by the Financial Services Authority in the Capital Market according to positive law in Indonesia, namely Revising Law No. 8 of 1995 concerning Capital Markets. Revised Law Number 21 the Year 2011 concerning the Financial Services Authority. The supervisory mechanism carried out by the OJK is to use a system of supervisory tools and supervisory action covering various checks such as securities transactions, securities agency compliance, investment management compliance, issuer compliance, and professional and supporting institutions compliance